Quantitative peripheral computed tomography to measure muscle area and assess lean soft tissue mass in children - Diana Paola Córdoba-Rodríguez; Iris Iglesia; Alejandro Gomez-Bruton; María L Miguel-Berges; Paloma Flores-Barrantes; José Antonio Casajús; Luis A. Moreno; Gerardo Rodríguez (Taylor & Francis Group, 2021)
Background Skeletal muscle is one of the main components of lean soft tissue mass (LSTM). Low levels in children affect locomotion, posture, and increase the risk of metabolic syndrome. Aim (1) To evaluate the association between muscle cross-sectional area (MCSA) of the lower left leg measured by peripheral quantitative computed tomography (pQCT) and total LSTM; namely, total left leg and left lower leg LSTM assessed by dual-energy X-ray absorptiometry (DXA) in a group of children, (2) to examine if MCSA is a predictor of LSTM, (3) to determine the ability of pQCT to identify children with low LSTM. Subjects and methods Lower left leg MCSA and LSTM were measured using pQCT and DXA, respectively, in 396 children. Results Statistically significant positive correlations were found between the lower leg MCSA - total LSTM (r² = 0.789), total leg LSTM (r² = 0.79), and lower leg LSTM (r² = 0.791) (p < .01). MCSA explained 64-68% of the variance in LSTM. Receiver operator characteristic (ROC) curves determined the capacity of the lower left leg MCSA to identify low LSTM in girls (AUC 0.95) and boys (AUC 0.87). Conclusions Our results showed that lower left leg MCSA, measured using pQCT, could be a tool to predict low LSTM in children.